2019
DOI: 10.2147/cmar.s190006
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical significance of systemic immune-inflammation index (SII) and C-reactive protein-to-albumin ratio (CAR) in patients with esophageal cancer: a meta-analysis</p>

Abstract: Background: Numerous studies have reported that systemic immune-inflammation index (SII) and C-reactive protein-to-albumin ratio (CAR) correlate with tumor progression and prognosis in various types of human cancer. The aim of this study is to systematically investigate the clinical significance of SII and CAR in esophageal cancer (EC). Methods: We searched a number of databases for articles reporting the effect of pretreatment SII and CAR on the survival of EC patients. Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 42 publications
3
36
1
Order By: Relevance
“…Thus, SII may be effective to reflect the inflammatory status which is an important mechanism for the development of cancers and may be an underlying biomarker for prognosis prediction. This hypothesis had been demonstrated in meta-analyses on lung cancer [23,24], esophageal cancer [25], gastrointestinal cancers [26], hepatocellular carcinoma [27], and several other cancer types [28,29]. All these meta-analyses showed that increased SII predicted poor prognostic outcomes for patients with cancers.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, SII may be effective to reflect the inflammatory status which is an important mechanism for the development of cancers and may be an underlying biomarker for prognosis prediction. This hypothesis had been demonstrated in meta-analyses on lung cancer [23,24], esophageal cancer [25], gastrointestinal cancers [26], hepatocellular carcinoma [27], and several other cancer types [28,29]. All these meta-analyses showed that increased SII predicted poor prognostic outcomes for patients with cancers.…”
Section: Discussionmentioning
confidence: 78%
“…However, both previous studies [29,30] and ours [31] documented that the predictive values of serum CRP and ALB as a single marker for initial IVIG resistance were not ideal. Notably, CAR as a ratio of CRP to ALB initially proposed by Fairclough [48], has been widely demonstrated to be more valuable and accurate than either CRP or ALB alone, providing a variable capable of merging information in the prediction of the systemic inflammatory state and prognosis in adverse cardiovascular events, cancers, inflammatory bowel disease, arteritis and critically ill septic patients [32][33][34][35][36][37][38][39][40][48][49][50][51]. In almost previous studies, CAR performed better predictive ability than either CRP or ALB alone, nonetheless, Cagdas et al found that CAR had better predictive accuracy than CRP but was not superior to ALB [52].…”
Section: Discussionmentioning
confidence: 99%
“…Examples include neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), lymphocyte-monocyte ratio (LMR), and systemic immune-inflammation index (SII) (8)(9)(10)(11)(12)(13). SII, which is calculated as platelet count × neutrophil count/lymphocyte count, has been recently shown to have a powerful prognostic value in several tumors including lung cancer (14), esophageal cancer (15), colorectal cancer (16), and hepatocellular carcinoma (17). Previous studies have also investigated the prognostic impact of SII on GC, but the results have been inconsistent (12,13,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%